Effects of public procurement policies on organizational performance: A case of Water Services Regulatory Board - Moturi, Nyaboke Joyce; Arasa, Robert; Ombui, Kepha (My University, 2013)
Water governance has been identified as a key issue in water resources management and in the processes of water supply service delivery. This is in recognition of the fact that, several trend sand factors are currently increasing the likelihood of a serious crisis in Kenya over the medium and long-term; one of which is the lack of accountability and transparency which exists at some levels within the water sector, leading to corruption. This study sought to investigate the effects of public procurement policies on organizational performance by focusing on WASREB. The objectives of this study were to establish the effects of public procurement policies on transparency and efficiency in service delivery of WASREB.This study used a case study design.The study population was 41 staff of WASREB. Since the study population was small, a survey design was used and the whole population was used in the study. Out of the study population of 41 respondents,40 responses were obtained which represent a 97.57% response rate.In collecting data, the study used semi structured questionnaires. The questionnaire was administered using a drop and pick later method to the sampled respondents. The quantitative data in this research was analyzed by use of descriptive and inferential statistics using statistical package for social sciences (SPPS). Descriptive statistics such as mean, frequency, standard deviation and percentages were used to profile sample characteristics and major patterns
Keywords: Public Procurement Policy; Transparency; Efficiency